WAHYU DAN HERMENEUTIKA Telaah Kritis atas Teori Diferensiasi Aksin Wijaya - Fadhli Lukman (Istitut Ilmu Al-Qur'an (IIQ) An-Nur Yogyakarta Komplek PP An Nur Ngrukem PO BOX 135 Bantul 55702 Yogyakarta Tlp/Fax (0274) 6469012. http://jurnalannur.ac.id/, 2012)
This article tries to study critically the Aksin Wijaya’s theory of revelation differentiation in terms of hermeneutics. In his explanation, the critical analysis works at two ways. First, it examines and tests the validity and plausibility of arguments used by Aksin in formulating his theory of differentiation. Second, it has criticism on relevance of the theory of differentiation with hermeneutics. To describe the theory of the differentiation, author uses the terminology of Revelation, the Qur’an, and Ottoman manuscripts. The result of analysis concludas; First, the structural-linguistic approach in the study of Ahsin Wijaya has implication for his rejection of the existence of Jibril in the communication process of revelation delivery. In addition, Aksin shows some misunderstandings the application of this method. Second, the theory of differentiation that is intended to defend the legality of hermeneutics to interpret the Qur’an is precisely not in accordance with what is required by the hermeneutics itself.